Osteoradionecrosis of the jaw: A mini review - Singh, Annu; Huryn, Joseph M.; Kronstadt, Kenneth L.; Yom, SaeHee K.; Randazzo, Joseph R.; Estilo, Cherry L. (Frontiers in Oral Health, 2022)
Osteoradionecrosis (ORN) of the jaw is one of the most dreaded complications of head and neck radiation therapy. Despite the evolution of radiation treatment modalities, ORN continues to remain a therapeutic challenge and its etiopathogenesis still remains unclear. It is clinically characterized by exposed necrotic bone within the head and neck radiation field. Over the past years, several studies have reported on the definition, staging, incidence, etiology, and management of this oral complication. In this review, we summarize the literature on ORN and discuss our institutional experience and management strategies that aim to predict and mitigate risk for ORN.